O problema da imaginação nas duas edições da "dedução transcendental das categorias" - Vaccari, Ulisses Razzante (Universidade Federal de São Carlos, 2008)
This thesis is designed to examine to what extent the meaning that in the 1781 issue was clearly assigned to transcendental imagination was changed by Kant in the second issue of the Critique of pure reason as of 1787. Obviously, the examination of imagination does not cover the Critique entirely; it is limited to the section transcendental deduction of the pure understanding concepts in which the philosopher provides elements for understanding not only the role assigned to imagination but also the other faculties of the anima. A comparison of both versions of this transcendental deduction is thus meant to show that the significance attributed by Kant to imagination in the 1781 transcendental deduction (A) is not lost when the afore-mentioned section is rephrased in 1787 (B). However, the basis for this is paragraph 10 of the Critique, i.e., the metaphysical deduction of categories, which goes to show that this paragraph already bears a systematic reading of the range of faculties, which permits the need for imagination to be seen in its task of synthesis of a general mannifold. It is this need for imagination in paragraph 10 that is intended to be shown in both versions of the transcendental deduction. Therefore, what would distinguish the approach to imagination between the latter and the former is that the former (A) had taken the path of the empiric genesis of representations, and for this very reason, is required to appoint imagination as the reproductive faculty avant-la-lettre. On the contrary, since in 1787 the philosopher was tending to advance to the opposite direction, namely, demonstrate the objective validity of representations, the deduction chooses to only expose imagination in its transcendental character to the extent that its boundaries with judgment get blurred.
Keywords: Filosofia - história; Filosofia moderna; Kant, Immanuel, 1724-1804; Imaginação (Filosofia); Imagem; Compreensão; CIENCIAS HUMANAS::FILOSOFIA